Experimental and numerical crack paths in PUR foams. (November 2016) - Marsavina, Liviu; Constantinescu, Dan M.; Linul, Emanoil; Stuparu, Florin A.; Apostol, Dragos A.
Highlights: Mixed mode fracture toughness determination of PUR foams. XFEM applied to simulate the crack initiation and propagation. Similar experimental and numerical crack paths were found. Abstract: In this paper is presented the behaviour of PUR foams under mixed mode loading. Closed cell rigid PUR foams having three different densities 100, 145, and 300 kg/m 3 were investigated. Experiments were performed using asymmetric semi-circular bend (ASCB) and Assymmetric Four-Point Bend (AFPB) specimens. The obtained crack initiation angles established for ASCB specimens were compared with four fracture criteria MTS, SED, Gmax and ESIF, and a good agreement was observed. When testing AFPB specimens, and calculating the normalized stress intensity factors it is important to obtain a correct crack propagation, that is to impose proper geometrical dimensions as not to affect the initial crack tip. The eXtended Finite Element Method (XFEM) is a complementary powerful numerical tool used to analyze crack initiation and propagation only if the numerical model is correctly calibrated and all the influencing parameters are properly understood.